Job Hopping and Economic Agglomeration in Germany - Michaela Fuchs (European Regional Science Association (ERSA), 2012)
This paper investigates whether labor mobility varies with the degree of agglomeration and, if so, how the differences can be explained. The theoretical basis rests on the advantages agglomerations exhibit in providing a large pooled labor market, one of Marshall's famous three sources of agglomeration economies. Only a small number of studies have so far investigated how the concentration of economic activity interacts with local labor market dynamics. They generally find support of the hypothesis that labor market pooling works better in agglomerations. Since most of the relevant literature is limited by sectoral and geographic restrictions, however, the question whether there exists a general relationship between job hopping and economic density still remains to be answered. This paper aims at answering this question and thus at contributing to the still sparse literature on the effect of both urban and industrial agglomeration on labor market pooling. Taking advantage of a unique and comprehensive data set on all establishments and employees for Germany that are subject to social security contributions, I exploit information on the movement of workers in and out of establishments as well as detailed information on worker and establishment characteristics. The analysis covers the years from 2001 to 2009 and is carried out for Germany on the level of NUTS3-regions and a disaggregated industry classification. In total, it contains information on roughly 29 million establishments and 291 million employees. First empirical results do not support the hypothesis that, in general, it is easier for employees to job hop in agglomerations than in rural areas. The data for all industries shows that, although job mobility tends to diminish with the degree of deagglomeration, in rural regions it is almost as high as in the dense core cities. This pattern is especially pronounced in the manufacturing sector, where labour turnover rates in the rural regions are 10 percentage points higher than in core cities. In the service sector, by contrast, labor mobility is indeed higher in agglomerated regions. This pattern can be regarded as a first hint in favor of the advantages of agglomerations in terms of labor market pooling. The relationships that emerged with respect to the broad sectoral classifications will be further investigated with the help of econometric techniques that also take into account the information on the establishment and worker characteristics.
Keywords: 330